Conserved regions upstream of BRC1B regulate bud dormancy in tomato - Hatinoğlu, Gül; van der Wal, Froukje; Angenent, Gerco C.; de Maagd, Ruud A.; Immink, Richard G.H. (Frontiers in Plant Science, 2025)
Plant architecture is majorly influenced by shoot branching through the development of axillary meristems in the leaf axils. These meristems develop into axillary buds, which are kept dormant until endogenous or exogenous cues allow their activation. The key TCP class II transcription factor (TF) BRANCHED1 (BRC1) regulates the early stages of bud outgrowth. BRC1 expression is highly specific to axillary buds, where it inhibits outgrowth by integrating hormonal, nutrient, and environmental signals. While the function of BRC1/TB1 genes is highly conserved in numerous species, the cis- and trans-regulation of BRC1 expression remains poorly understood. In this study, we explored how modifications in the SlBRC1B promoter affect bud outgrowth in tomato. We identified four highly conserved regions (CR1 to CR4) in the sequence upstream of the SlBRC1B translation start site by performing a phylogenetic footprinting. A collection of promoter mutants was generated by separately targeting each CR using CRISPR/Cas9. These CR mutants were employed for a detailed bud outgrowth characterization to investigate the effect of mutations on SlBRC1B-mediated bud dormancy. Most CR mutants consistently showed decreased bud outgrowth, suggesting that SlBRC1B is under tight control of various transcriptional repressors. Screening CR4 with an axillary bud-specific cDNA library in a Yeast one-hybrid assay identified MYB, GRF, NAC, MADS, and zinc finger TF family members. Based on our findings, we concluded that the identified CRs play a crucial role in regulating SlBRC1B expression, and that they could be strategically targeted to achieve a desired level of shoot branching.